Pathway selection as a tool for crystal defect engineering: A case study with a functional coordination polymer. (September 2020) - Abrishamkar, Afshin; Suárez–García, Salvio; Sevim, Semih; Sorrenti, Alessandro; Pons, Ramon; Liu, Shi-Xia; Decurtins, Silvio; Aromí, Guillem; Aguilà, David; Pané, Salvador; deMello, Andrew J.; Rotaru, Aurelian; et al.
Abstract: New synthetic routes capable of achieving defect engineering of functional crystals through well-controlled pathway selection will spark new breakthroughs and advances towards unprecedented and unique functional materials and devices. In nature, the interplay of chemical reactions with the diffusion of reagents in space and time is already used to favor such pathway selection and trigger the formation of materials with bespoke properties and functions, even when the material composition is preserved. Following this approach, herein we show that a controlled interplay of a coordination reaction with mass transport (i.e. the diffusion of reagents) is essential to favor the generation of charge imbalance defects (i.e. protonation defects) in a final crystal structure (thermodynamic product). We show that this synthetic pathway is achieved with the isolation of a kinetic product (i.e. a metastable state), which can be only accomplished when a controlled interplay of the reaction with mass transport is satisfied. Accounting for the relevance of controlling, tuning and understanding structure-properties correlations, we have studied the spin transition evolution of a well-defined spin-crossover complex as a model system. Graphical abstract: Here, we present pathway selection as new synthetic route to achieve defects in a functional crystal, namely a well-known spin crossover complex. Notably, it has been demonstrated that this synthetic pathway also leads to unprecedented physico-chemical properties of the final thermodynamic product upon annealing of an unprecedented crystalline metastable state. Image, graphical abstract